PERUBAHAN SERAGAM TOKOH LIGHT DALAM DEATH NOTE FILM VERSI NETFLIX - Honesty Audi; Nungki Heriyati (Program Studi Sastra Jepang, Universitas Komputer Indonesia Bandung, 2019)
Death Note yang dibuat oleh Tsugumi Ohba dan diilustrasikan oleh Takeshi Obata yang dibuat ulang oleh Netflix pada 2017. proses remake mengubah beberapa aspek cerita, salah satunya adalah perubahan dalam karakter utama, Light. One of the changes that can be seen is Light’s fashion to school. These changes are influenced by cultural differences due to changes in place settings in the story. By using the theory of cultural change proposed by Julian Steward, this study will be analyzed descriptively using a qualitative method. The data in this study were obtained from the anime Death Note made in Japan and the film Death Note version of Netflix. From the research conducted, it was found that there was a change in the way of dressing Light Yagami and Light Turner to school. This can be seen from the uniform rules in the two very different countries, between United State and Japan. There is a cultural adaptation that occurs in the making of the film Death Note Netflix version. Keywords : Death Note, Adaptation, Culture, Fashion